Pre-Hospital Delaying Factors in Patients of Acute Ischemic Stroke who are Candidates for Thrombolytic Therapy - Ali, Kamran; Nawaz, Khurram Haq; Hassan, Wahaj Ul; Waqar, Raja Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To identify and statistically evaluate pre-hospital delaying factors for thrombolysis in Acute Ischemic Stroke (AIS). Study Design: Cross-sectional study. Place And Duration OF Study: Emergency/Neurology Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Dec 2020 to Mar 2021. Methodology: Patients older than 18 years and who reported to the emergency/Neurology clinic with stroke symptoms were included in the study. The patients or their relatives were interviewed with a detailed questionnaire that recorded patients’ National Institute of Health Stroke Scale and other socio-demographic variables. In addition, the patients were grouped based on time of arrival to the hospital: Early (<4.5 hours) and Late (>4.5 hours), and the variables recorded were compared with each other. Results: Of 98 patients, 71(72.5%) arrived early, and 27(27.5%) arrived late. Seventy patients (72%) were male, and 28(28%) were female. Only 18 patients availed of the ambulance service, whereas the rest of the study participants reached the hospital using private transportation. Conclusion: Female gender, NIHSS score of 10 or below and using transport other than ambulance adversely affect the hospital arrival time of acute ischemic stroke patients.